2015
DOI: 10.2113/econgeo.110.6.1541
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric Architecture of the Lhasa Terrane and Its Control on Ore Deposits in the Himalayan-Tibetan Orogen

Abstract: Magmatic-hydrothermal ore deposits in collisional orogens are new targets for modern mineral exploration, yet it is unclear why they preferentially occur in some specific tectonic environments within these orogenic belts. We integrate geologic and geochemical data (especially zircon U-Pb dating and Lu-Hf isotope data) for Mesozoic-Cenozoic magmatic rocks and associated ore deposits in the Lhasa terrane, a highly endowed tectonic unit within the Himalayan-Tibetan orogen, and provide the first example in a conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
209
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 410 publications
(215 citation statements)
references
References 132 publications
(219 reference statements)
6
209
0
Order By: Relevance
“…However, to understand the regional evolution, it is crucial to determine whether ancient lithosphere existed beneath the Lhasa Terrane. Previous studies suggested there was ancient lithosphere beneath the Lhasa Terrane, based on the Nd, Pb, and Hf isotopic model ages of postcollisional potassic and ultrapotassic rocks (Hou et al, ; Miller et al, ; Turner et al, ). Zhu et al () stated that the Lhasa Terrane has ancient basement rocks with Proterozoic and Archean ages in its center, with younger or juvenile Phanerozoic crust accreted to its northern and southern edges.…”
Section: Discussionmentioning
confidence: 99%
“…However, to understand the regional evolution, it is crucial to determine whether ancient lithosphere existed beneath the Lhasa Terrane. Previous studies suggested there was ancient lithosphere beneath the Lhasa Terrane, based on the Nd, Pb, and Hf isotopic model ages of postcollisional potassic and ultrapotassic rocks (Hou et al, ; Miller et al, ; Turner et al, ). Zhu et al () stated that the Lhasa Terrane has ancient basement rocks with Proterozoic and Archean ages in its center, with younger or juvenile Phanerozoic crust accreted to its northern and southern edges.…”
Section: Discussionmentioning
confidence: 99%
“…The North Lhasa subterrane [including the central and north Lhasa subterranes of Zhu et al []] also documents long‐term Mesozoic–Cenozoic magmatism, associated with either southward subduction of Bangong‐Nujiang oceanic lithosphere in the north [e.g., Zhu et al, ] or northward subduction of the Neotethyan oceanic lithosphere in the south [e.g., P. Kapp et al , ]. Geochronological studies have revealed a magmatic flare up at 113 ± 5 Ma [ Hou et al , ]. Igneous rocks in the North Lhasa subterrane commonly yield enriched Hf isotopes indicating re‐melting of older crust [e.g., Chu et al , ; Chiu et al , ; Zhu et al , ].…”
Section: Geological Settingmentioning
confidence: 99%
“…1). Recently, Hf isotope mapping of the whole Lhasa terrane revealed three distinct crustal blocks: a Precambrian microcontinent in the center (central Lhasa subterrane) and reworked juvenile Mesozoic crustal blocks on the two sides (the northern and the southern Lhasa subterrane, Zhu et al 2011a andHou et al 2015). The Precambrian central Lhasa subterrane has Archean and Proterozoic crystalline basement, which rifted from the Gondwana margin in the Carboniferous-Middle Permian ).…”
Section: Geological Settingmentioning
confidence: 99%